Sistem Pemerintahan dan Pranata Politik Timur Tengah - Hamdi, Zainal; Nurwahidin, Nurwahidin; Hannase, Mulawarman; Lubis, Amany Burhanuddin Umar (Jurnal ICMES, 2024)
The decades-long Israeli-Palestinian conflict has become one of the most complex and significant geopolitical issues, with far-reaching implications for political stability in the Middle East. This study aims to identify the roots of the conflict, the factors that influence it, and its impact on the region's governance system and political institutions. This study uses qualitative methods with a descriptive-analytical approach, which provides an in-depth understanding of both parties' internal dynamics and the conflict's impact on regional stability. The results show that the governance systems of both countries play an important role in this dynamic. Israel can maintain stability through a parliamentary democratic system supported by checks and balances mechanisms. In contrast, in Palestine, along with the continuing occupation by Israel and the absence of sovereignty, a dualism of power has emerged, namely the Palestinian National Authority in the West Bank and Hamas in Gaza. This dualism has triggered internal fragmentation that has hampered the effectiveness of government and added to the complexity of efforts to achieve independence. Furthermore, this conflict has also caused political instability at the regional level and complicated the foreign policies of countries in the region.